RELATIONSHIP BETWEEN FAMILY KNOWLEDGE ABOUT IRON CHELATION AND ADHERENCE TO GIVING IRON CHELATION IN CHILDREN WITH THALASSEMIA AT RSCM KIARA - Setiyadi, Agung; Intan Parulian; Muhammad Ulfan (Fakultas Kesehatan Masyarakat Universitas Muhammadiyah Jakarta, 2022)
Based on a preliminary study by conducting interviews with 10 families of thalassemia patients at RSCM Kiara. It was found that only 40 % were obedient in giving iron chelation to thalassemia patients. This study aimed to find the relationship between family knowledge about iron chelation and adherence to consuming iron chelation in children with thalassemia. The method used in this study was a descriptive non-experimental method with a cross-sectional approach. Data analysis techniques in this activity are presented as descriptive and bivariate analysis using Spearman's rho statistical test with = 0.05. It measures the level of adherence to taking medication using the Morisky Medication Adherence Scale (MMAS-8) questionnaire. Based on the results of measuring respondents' knowledge level, 85.5% of respondents have a good level of knowledge 14.5% of respondents have a sufficient level of knowledge. Measuring the level of adherence to medication, 22.9% of respondents have high adherence to drug consumption, 42.2% of respondents have a moderate level of adherence to drug consumption, and 34.9% have a low adherence to drug consumption. There is significant relationship between the knowledge level about iron chelation and adherence to giving iron chelation (p-value 0.006 <0.05 and r-value of 0.30). But the relationship is low, so knowledge about iron chelation alone is not enough to make adherence to giving iron chelation in children with high adherence results.